Gambaran Waktu Tunggu Pada Pelayanan Rawat Jalan dan Tingkat Kepuasan Pasien Peserta BPJS di RSU Prasetya Bunda Tasikmalaya - Andi Suhenda; Anjani, Santi Puspa (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2024)
Background: Service waiting time is the time a person takes to receive health services from registration to entering the doctor's examination room. The availability of services, identified by the short patient waiting time, is one of the characteristics of the quality of health services, the quality of health services refers to the dimensions of the quality of health services, which in turn results in patient satisfaction. Research Methods: This type of research is quantitative research with a descriptive approach to the sampling technique used, namely Incidental Sampling. The total population is 30,075 and the number of samples in this study is 100 respondents calculated using the slovin formula. Research Results: The results of the research on waiting time in outpatient services as many as 86 respondents (86%) were in accordance with the standards and as many as 14 respondents (14%) did not comply with the standards. The results showed that patient satisfaction out of 100 respondents to outpatient services in general, all service dimensions were included in the satisfaction category, with the percentage of patients who were satisfied as many as 84 respondents (84%) and patients who were dissatisfied as many as 16 respondents (16 %). Conclusion: The waiting time for outpatient services is more in accordance with the standards, and for the patient satisfaction of BPJS participants in outpatient services, in general, the patients are satisfied. Keywords: Patient Satisfaction, Outpatient, Waiting Time.